Pengaruh Media Leaflet Terhadap Pengetahuan Tentang Pencegahan Kehamilan Usia Remaja - Nurannisa Fitria Aprianti; Eka Faizaturrahmi; Marisa Marcelina Limbong (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
Pregnancy in adolescence is still a public health problem that has an impact on increasing maternal and infant health risks and causes psychosocial and social consequences. The low level of adolescent knowledge about reproductive health and the prevention of teenage pregnancy is one of the factors that affects the high incidence of these events. This study aims to analyze the influence of leaflet media on adolescents' knowledge about adolescent pregnancy prevention. This study uses a quantitative approach with a pre-experimental design: a one-group pretest–posttest without a control group. The sample consisted of 81 students in class X at SMA Negeri 1 Pringgabaya, selected using systematic random sampling. The intervention was carried out through leaflet-based reproductive health education. Data were collected using a structured questionnaire and analyzed using the Wilcoxon test. The results of the study showed an increase in adolescent knowledge after the intervention. The proportion of respondents with a good level of knowledge increased from 11.1% in the pretest to 79.0% in the posttest, while the category of less knowledge decreased from 70.4% to 6.2%. Statistical analysis showed a significant difference between the level of knowledge before and after the intervention (p = 0.000).